UJI FITOKIMIA, TOKSISITAS DAN AKTIVITAS ANTIOKSIDAN PADA EKSTRAK ETANOL DAUN SIRSAK (Annona Muricata L.) - Shadrina, Alyani Nur; Tomagola, Azmi Sakina; Ramadhandita, Jauzaa Lisgia; Erwin, Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Sirsdak (Annona muricata L.), is a plant whose fruit is edible and the leaves and fruit have been used by the community as traditional medicine. This study aims to test the chemical content, toxicity, and antioxidant activity of ethanol extract of soursop leaves (Annona muricata L.). Phytochemical tests were carried out to identify bioactive compounds contained in the extract, while toxicity tests used the Brine Shrimp Lethality Test (BSLT) method to determine toxic potential. Antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method to measure the ability to scavenge free radicals. The results showed that the ethanol extract of soursop leaves contained steroid, saponin and quinone compounds, had significant toxicity potential with an LC50 value of 31.19 ppm, and showed weak antioxidant activity with an IC50 value of 111.27 mg/L Keywords : Soursop Leaves., Phytochemical Analysis Antioxidant and Toxicit.